Пошаговое объяснение:
1. подстановки:
║ х - у = 4,
║ х² - 2у = 11,
из 1 ур-ия:
х = у + 4,
подставим во 2 ур-ие:
(у+4)² - 2у = 11,
у² + 8у + 16 - 2у = 11,
у² + 6у + 5 = 0,
Д = 6² - 4*1*5 = 36 + 20 = 16,
у1 = (-6 + 4) / 2*1 = -2/2 = -1,
у2 = (-6 - 4) / 2*1 = -10/2 = -5,
х1 = -1 + 4 = 3,
х2 = -5 + 4 = -1,
2. сложения:
║ х - у = 4, (х -2)
║ х² - 2у = 11,
║ -2х + 2у = -8,
║ х² - 2у = 11,
-2х + 2у + х² - 2у = -8 + 11,
-2х + х² = 3,
х² - 2х - 3 = 0,
Д = (-2)² - 4*1*(-3) = 4 + 12 = 16,
х1 = (2 + 4) / 2*1 = 6/2 = 3,
х2 = (2 - 4) / 2*1 = -2/2 = -1,
из 1 ур-ия:
у = х - 4,
у1 = 3 - 4 = -1,
у2 = -1 - 4 = -5,
3. графически:
решение на фото
⇅ ⇅ ⇅
ответ: (3; -1), (-1; -5)
Пошаговое объяснение:
1. подстановки:
║ х - у = 4,
║ х² - 2у = 11,
из 1 ур-ия:
х = у + 4,
подставим во 2 ур-ие:
(у+4)² - 2у = 11,
у² + 8у + 16 - 2у = 11,
у² + 6у + 5 = 0,
Д = 6² - 4*1*5 = 36 + 20 = 16,
у1 = (-6 + 4) / 2*1 = -2/2 = -1,
у2 = (-6 - 4) / 2*1 = -10/2 = -5,
х1 = -1 + 4 = 3,
х2 = -5 + 4 = -1,
2. сложения:
║ х - у = 4, (х -2)
║ х² - 2у = 11,
║ -2х + 2у = -8,
║ х² - 2у = 11,
-2х + 2у + х² - 2у = -8 + 11,
-2х + х² = 3,
х² - 2х - 3 = 0,
Д = (-2)² - 4*1*(-3) = 4 + 12 = 16,
х1 = (2 + 4) / 2*1 = 6/2 = 3,
х2 = (2 - 4) / 2*1 = -2/2 = -1,
из 1 ур-ия:
у = х - 4,
у1 = 3 - 4 = -1,
у2 = -1 - 4 = -5,
3. графически:
решение на фото
⇅ ⇅ ⇅
ответ: (3; -1), (-1; -5)
9) 9[x]-6=0
9[x]=6
[x]=2/3
x=2/3, x=-2/3
10) 8/x=6/5
6x=40
x=40/6
x=20/3
x=6 2/3
19) 2m/3 - 4m/5 =3
10m-12m=45
-2m=45
m=-45/2
m= -22,5
20) 4a/9 - 1 = 5a/12
16a - 36 = 15a
16a - 15a = 36
a=36
21) 3-3x+5x+10=1-4x
13+2x=1-4x
2x+4x=1-13
6x=-12
x=-2
22) 6-3x-5x-4=0.4-16x
2-8x=0.4-16x
16x-8x=0.4-2
8x=-1.6
x= -0.2
23) 6-10p=4-4p-1
6-10p=3-4p
-10p+4p=3-6
-6p=-3
p=0.5
24) y-0.5-0.5+0.2y+1=0
1.2y+0=0
1.2y=0
y=0
25) -20+8m+3m-12=12-6m-5m
-32m+11m=12-11m
11m+11m=12+32
22m=44
m=2
26) 0.9x-0.3+0.2=0.5-x-0.1
0.9x-0.1 = 0.4-x
0.9x+x=0.4+0.1
1.9x=0.5
x= 5/19